The Effect of Partial Splenectomy on Platelet Production in Mice - Bessler, H; Notti, I; Djaldetti, M (Thrombosis and Haemostasis, 1981)
The effect of total and partial splenectomy on the number and production of circulating platelets was studied in mice. Five days after total and partial splenectomy the number of the peripheral blood platelets increased by 87% and 60%, respectively and the incorporation of 75selenium methionine (75Se-Met) into platelets was enhanced indicating that the thrombocytosis was due to increased platelet production. The results obtained by the two operative procedures were compared.Since previous work from our laboratory has shown that a factor produced by splenic lymphocytes affects the platelet number in mice, it is suggested that the differences in the number of circulating platelets observed in animals after total and partial splenectomy may reflect a difference in the number of spleen lymphocytes removed.
Keywords: Partial splenectomy; Platelets; Thrombocytosis